The effect of season on the microbiological status of raw milk - Szabóné Petróczki, Flóra Mária; Béri, Béla; Peles, Ferenc (Acta Agraria Debreceniensis, 2020)
Many factors can influence the microbiological quality of raw cow’s milk. In this study, our aim was to determine whether there was any difference between the microbiological statuses of milk produced in different seasons. Samples were collected and analysed from five dairy farms in Hajdú-Bihar County, from February to November in 2019. During our studies, total plate count (TPC), coliform count and Staphylococcus aureus count of raw cow’s milk samples were determined.There was no significant difference (P>0.05) between the mean TPC values detected in the milk collected in winter and autumn, but that values were significantly (P